Does Corruption Impact On Firms' Ability To Conduct Business In Mauritania ? : Evidence From Investment Climate Survey Data - Francisco, Manuela (The World Bank, 2008)
This paper seeks to understand whether Mauritanian firms deem corruption as an obstacle to operate and grow, to identify the profile of firms that are more likely to make informal payments, and to quantify the size of these payments. The results of the analysis show that perceptions of corruption can be potentially misleading. Corruption is not considered to be one of the most taxing factors impeding the growth of firms in Mauritania. Yet, its cost to firms is significant and greater than in the comparator group countries. This means that corruption is internalized by firms and considered an accepted practice. Alternatively, firms may fear reporting corruption practices for fear of retaliation. Econometric evidence on the propensity and intensity of bribes suggests that medium-size firms suffer the most from corruption in Mauritania. Larger firms are more established and connected, do not fear exiting the market, and are less likely to be harassed. Smaller firms are less visible and may be able to escape the control of public officials by operating largely in the informal sector. Medium-size firms are the most likely to pay bribes and to pay the highest amounts as a percentage of their total annual sales, which places a heavy burden on their ability to grow